(untitled) (International conference on multidisciplinary science, 2023)
The acquisition by students of chemical knowledge that serves the development of society at educational stages occurs during the implementation of chemical education. Formative and standardizing instruments of chemical education include the specialization of general, secondary specialized vocational education, the State educational standard and curriculum, the natural sciences program and textbooks. The state educational standard determines the limits of chemical knowledge, skills and competencies that students can acquire, professional factors and subjects that contribute to the development of society and the acquisition of chemical knowledge, and reflects their chosen specialty in the curriculum included in the educational program. DTS.